Laboratorijski testi kot pomoč pri ocenjevanju zmogljivosti potapljačev - Kapus, Jernej (Šport (Ljubljana), 2013)
Last year, the process of testing of apnea divers was started in the Laboratory of Biodynamics. The abilities of two Slovenian elite apnea divers were regularly monitored throughout the competitive season. Due to the fact that physical improvements - including increased pulmonary volumes, expiratory muscle strength and diving responses during apnea with face immersion - depend on the nature of training program, the purpose of those testings was to help them at their training plan. The aim of the paper is to present the tests, our first experiences and further challenges.
Keywords: apnea diving; apnea with face immersion; moč izdišnih mišic; potapljanje; sport; strength of inspiratory muscles; šport; testing; testiranje; zadrževanje diha